Mapping of Green Sukuk Research (2014 - 2023) : With Vosviewer Bibliometric and Literature Review - Doni Yusuf Bagaskara; Nanik Wahyuni; Meldona (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2024)
This study aims to determine the mapping of research around Green Sukuk. The approach used is a mix-method approach, namely VOSviewer bibliometric studies and literature review. Data analysis techniques include: (1) mapping the number of journal publications distributed around green sukuk using Microsoft Excel and Mendeley Desktop based on the year of publication; (2) mapping the results of bibliometric network visualization and journal publication trends around green sukuk using VOSviewer (Visualization of Similarities) algorithm software based on the number of clusters and their items; and (3) mapping research topics around green sukuk using literature studies. The results showed that: (1) based on mapping the number of journal publications, there were 168 journal publications about green sukuk; (2) based on the mapping of VOSviewer bibliometric studies, the results of network visualization around green sukuk are divided into 5 clusters and 24 topic items (3) Based on the mapping of the literature review study, there are 2 topics about green sukuk that often appear, first green sukuk and second Indonesia. The implication and contribution of this research is to map research topics around green sukuk in the world that are often or rarely researched by researchers, so that they can be a reference for researchers afterwards.